Educação escolar quilombola no Cariri Cearense: africanização da escola a partir de pedagogias de quilombo - Santos, Ana Paula dos (2018)
The quilombola school education is a right to be guaranteed to the black population, who live in territories of African reminiscence, to study in schools located geographically in these spaces, next to them or that receives quilombola, must consider in the curriculum school, the ethnic, historical aspects, anthropological and cultural community. These communities are strongly marked by the presence of African culture and constitute the material and immaterial patrimony of Brazil. The historical and identity elements that make up the formation of quilombos are found in the quilombola community of Carcará, municipality of Potengi in the region of Cariri, in the southern state of Ceará. The focus of this research is defined, based on a work focused on the curricular Africanization of the quilombola school Maria Virgem da Silva, marked by a quilombo pedagogy. This work proposal, aims to investigate factors of the Afrocarian cultural repertoire are important for the quilombola school curriculum in the community in question, having as reference, Law 10.639 / 03, which established the obligation of teaching African and Afro-Brazilian history in all curricula of basic education, and the National Curricular Guidelines for Kildorn School Education of 2012, and from that, to build with the teachers a curricular guideline that guides the work in the school. In the unfolding, from this objective I initially adopted the observation research, begun at the end of the year 2014 and beginning of 2015, the conclusion of a specialization course for the pedagogical management of said school and the analysis of the results revealed a curriculum that did not dialogue with the quilombola knowledge, it is from this problematization that the intervention research originates from the collection of data made from the methodological instruments of field diary, interviews and observation. The theoretical framework is made up of authors such as Cunha Junior (2007), Kabenguele Munanga and Gomes (2006), Anjos (2006), Macedo (2006), Videira (2013) and Nascimento (2006) who discuss the conceptual categories necessary for theoretical enrichment of the research, categories as: quilombo, identity, territory, memory quilombola and pedagogy of quilombo. The dissertation also deals with the various elements of the Caririan Africanities, and promotes a dialogue with geographical, historical and archaeological studies of the region. The study allowed us to conclude that it is urgent that quilombola schools need to develop ethnic pedagogical work through quilombo pedagogies.